Influence of partial shear connection on the behaviour of U-shaped steel concrete beams with L-shaped shear connectors. (1st March 2023) - Lepourry-Nicollet, Clemence; Heng, Piseth; Somja, Hugues; Palas, Franck
Highlights: The influence of partial shear connection on the behaviour of the USCB with L-shaped shear connectors. Three full-scale tests on the USCB with a degree of shear connection ranging from 0.4 to 1 under sagging bending moment. A two-layer beam element formulation taking into account the interlayer slips in a co-rotational framework was also adapted. A parametrical study is also carried out to investigate the effect of important parameters on the behaviour of the USCB. Abstract: This paper presents a study on the influence of partial shear connection on the behaviour of the U-shaped steel concrete beams (USCB) with L-shaped shear connectors. An experimental campaign of three full-scale experimental tests on the USCB with a degree of shear connection ranging from 0.4 to 1 has been conducted under sagging bending moment. The test results showed high ductility of the USCB with both full and partial shear connections. The failure mode of the USCB was governed by the plastic buckling of the upper flanges of the U-shaped steel profile at the location of the shear connectors. The plastic moment resistance of the USCB with partial shear connection predicted by the full plastic analysis approach and by the simplified approach in Eurocode 4 agreed well with the experimental results. Furthermore, the flexural stiffness of the USCB with partial connections predicted by American and Australian standards fit well with the experimental results. A numerical model based on the two-layer beam element formulation taking into account the interlayer slips with continuous connection in a co-rotational framework was also adapted to determine the behaviour of the USCB. This model was validated against experimental tests as well as against the analytical approaches. It was finally used to carry out a parametrical study in order to investigate the effect of selected parameters such as the degree of shear connection, the concrete strength and the steel strength of U-shaped profile.